2007
DOI: 10.1143/jjap.46.4948
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact Acoustic Manipulation in Air

Abstract: A noncontact manipulation technique is useful for micromachine technology, biotechnology, and new materials processing. In this paper, we describe an advanced manipulation technique for transporting small objects in air. A standing wave field was generated by two sound beams crossing each other generated by bolted Langevin transducers. Expanded polystyrene particles were trapped at the nodes of the sound pressure in the standing wave field. The position of a trapped particle was shifted by changing the phase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 7 publications
1
69
0
Order By: Relevance
“…This extends the capability of the present concept beyond the handling of spherical or nearspherical particle and droplet transport and to the controlled motion of very elongated, wire-like objects. As a result, an extremely elongated object with a characteristic length L much larger than λ can be levitated, propelled, transported, and rotated in a controllable manner, going beyond the widely accepted limit (9,11,14,15,27) of λ/2 for the maximum size of an acoustically levitated sample (Fig. 4 and Movie S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This extends the capability of the present concept beyond the handling of spherical or nearspherical particle and droplet transport and to the controlled motion of very elongated, wire-like objects. As a result, an extremely elongated object with a characteristic length L much larger than λ can be levitated, propelled, transported, and rotated in a controllable manner, going beyond the widely accepted limit (9,11,14,15,27) of λ/2 for the maximum size of an acoustically levitated sample (Fig. 4 and Movie S11).…”
Section: Resultsmentioning
confidence: 99%
“…Although significant progress has been made in the handling of microsized particles suspended in a liquid (12,13), where buoyancy forces are almost entirely responsible for the levitation, various drawbacks in the state of the art of acoustic levitation have prohibited the realization of controlled and reliable transport of matter in air, thereby limiting the remarkable potential and utility of acoustic levitation (14)(15)(16). Its full exploitation requires fundamental advances leading to material transport with high controllability and movement resolution, long transport length, versatility, and multidimensionality.…”
mentioning
confidence: 99%
“…Acoustic manipulation techniques have been investigated by several researchers [1][2][3][4]. Kozuka et al reported noncontact manipulation of particles in air by controlling the phase difference between two transducers [5]. We have also reported noncontact transport of small objects in air over long distances using a bending vibrator and a reflector [6] and transport in a circular trajectory [7].…”
Section: Introductionmentioning
confidence: 72%
“…Eq. (3) indicates that the superposition of the forward and reflected sinusoidal waves is the localized wavepacket represented as the sound pressure evolution in time and space. It is obvious that the sum of two sine functions belongs to new kind of solution rather than simple sine function.…”
Section: Resultsmentioning
confidence: 99%
“…Noncontact manipulation techniques are useful for micromachinery technology, biotechnology and new material processing. In the paper [3] advanced manipulation technique for the transport of small objects in the air is described. The standing wave has been created by two sound beams that cross each other, created by bolted Langevin transducers.…”
Section: Introductionmentioning
confidence: 99%